Eksplorasi Sentimen Pengguna Media Sosial Terhadap Layanan Seabank: Pendekatan Dengan Algoritma Bert - Septiani, Riska Kurnia; Gata, Windu (STMIK Banjarbaru, 2024)
Bank SeaBank is a digital bank that has social media accounts on Twitter (X) and YouTube with thousands of followers. These platforms are often used to express opinions or comments on various topics. This research aims to provide a benchmark for Bank SeaBank to improve its services based on positive and negative user reviews. The data analyzed consists of 500 comments on Twitter (X) and YouTube with the keyword